Distinguished Asian Americans : a biographical dictionary - Kim, Hyung-chan (Greenwood Press, 1999)
This is a resource of biographical profiles of noted Asian Americans, celebrating the contributions of 166 distinguished Asian Americans. The work represents more than 75 fields of endeavour, featuring both prominent and less familiar individuals.